Enhancing grant-writing expertise in BUILD institutions: Building infrastructure leading to diversity. - Robert A Hiatt; Yazmin P Carrasco; Alan L Paciorek; Lauren Kaplan; Marc B Cox; Carlos J Crespo; Andrew Feig; Karsten Hueffer; Harris McFerrin; Keith Norris; Elizabeth Roberts-Kirchhoff; Carrie L Saetermoe; et al. (PLoS ONE)
Background The lack of race/ethnic and gender diversity in grants funded by the National Institutes of Health (NIH) is a persistent challenge related to career advancement and the quality and relevance of health research. We describe pilot programs at nine institutions supported by the NIH-sponsored Building Infrastructure Leading to Diversity (BUILD) program aimed at increasing diversity in biomedical research. Methods We collected data from the 2016-2017 Higher Education Research Institute survey of faculty and NIH progress reports for the first four years of the program (2015-2018). We then conducted descriptive analyses of data from the nine BUILD institutions that had collected data and evaluated which activities were associated with research productivity. We used Poisson regression and rate ratios of the numbers of BUILD pilots funded, students included, abstracts, presentations, publications, and submitted and funded grant proposals. Results Teaching workshops were associated with more abstracts (RR 4.04, 95% CI 2.21-8.09). Workshops on grant writing were associated with more publications (RR 2.64, 95% CI 1.64-4.34) and marginally with marginally more presentations. Incentives to develop courses were associated with more abstracts published (RR 4.33, 95% CI 2.56-7.75). Workshops on research skills and other incentives were not associated with any positive effects. Conclusions Pilot interventions show promise in supporting diversity in NIH-level research. Longitudinal modeling that considers time lags in career development in moving from project development to grants submissions can provide more direction for future diversity pilot interventions.